Hubungan dukungan organisasi, kepuasan kerja, dan organizational citizenship behavior: pendekatan partial least square - Pingki Rizki Cahyani; Hendryadi Hendryadi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2018)
This study aims to examine the relationship of perceptions of organizational support (POS), job satisfaction and organizational citizenship behavior (OCB) in the government sector. The survey approach was carried out to obtain data through questionnaires. A total of 60 employees were used as research samples. Partial least square structural equation modeling (PLS-SEM) is used to test hypotheses. The results showed that: there was a positive relationship between POS and job satisfaction and OCB, job satisfaction was significantly correlated with OCB. In addition, job satisfaction has proven to play a role as a mediator for POS relations with OCB. This research contributes to efforts to increase OCB in the government sector,